MEMPERKUAT TATA KELOLA SUMBER DAYA LAUT YANG ADAPTIF MELALUI PEMBELAJARAN SOSIAL KOMUNITAS PRAKTIK MULTI-STAKEHOLDER DI PULAU BINTAN UTARA - Tri Samnuzulsari; Siti Arieta; Athika Thahira; Imam Yudhi Prastya; Edison Edison (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
The management of marine resources in small island regions is often hampered by fragmented knowledge systems, overlapping institutional mandates and a lack of coordination among stakeholders, which hinders the development of effective and adaptive governance. This article highlights how social learning within a Community of Practice (CoP) involving various stakeholders contributes to strengthening marine resource governance in this context. This study adopts a qualitative case study approach focusing on the Jaringan Peduli Laut (JALA) in North Bintan Island, Indonesia. Data were collected through in-depth interviews, focus group discussions (FGDs), and field observations, enabling a deep understanding of the processes of interaction and collaborative practices amongst the actors. Findings indicate that social learning emerges through sustained interaction, reflective dialogue, and repeated collective practices involving civil society organisations, local communities, government agencies, and academic actors. These processes facilitate the integration of local ecological knowledge with scientific perspectives, whilst fostering trust, shared understanding, and distributed leadership across the network. CoPs evolve beyond knowledge-sharing platforms into mechanisms that strengthen collective capacity to support joint adaptive management. This is evident in the emergence of community-based conservation initiatives, improved coordination in addressing coastal environmental challenges, and the gradual strengthening of institutional legitimacy at the local level. Although there have been positive developments, several challenges remain, including disparities in organisational capacity, communication barriers, and the differing interests of stakeholders that continue to shape the direction of collaboration.